The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1107/s010876819001076x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution neutron powder diffraction studies of the structure of CsDSO4

Abstract: High-resolution neutron powder diffraction data were used to determine the crystal structure of the superionic conductor CsDSO4 at 300K (lowconductivity phase) and at 448 K (superionic phase). A full structural analysis was performed, using the Rietveld method, to obtain previously unknown atomic positions, site occupancies and temperature factors for the light atoms. The mechanism of deuterium diffusion is discussed. At 300 K: monoclinic, P2~/c, a = 7.78013 (9), b = 8.13916 (2), c = 7.72187 (9) A, fl = 110.87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 6 publications
4
51
0
Order By: Relevance
“…The arrangement of Cs cations and XO 4 anions in Cs 2 (HSO 4 )(H 2 PO 4 ) is very similar to that in -Cs 3 (HSO 4 ) 2 (H 2 À x (S x P 1 À x )O 4 ) , -Cs 3 (HSO 4 ) 2 (H 2 PO 4 ) and CsHSO 4 (II) (Belushkin et al, 1991). All three of these compounds are also based on zigzag Cs and XO 4 chains, which again alternate in a checkerboard fashion.…”
Section: Comparison To Related Structuresmentioning
confidence: 73%
See 1 more Smart Citation
“…The arrangement of Cs cations and XO 4 anions in Cs 2 (HSO 4 )(H 2 PO 4 ) is very similar to that in -Cs 3 (HSO 4 ) 2 (H 2 À x (S x P 1 À x )O 4 ) , -Cs 3 (HSO 4 ) 2 (H 2 PO 4 ) and CsHSO 4 (II) (Belushkin et al, 1991). All three of these compounds are also based on zigzag Cs and XO 4 chains, which again alternate in a checkerboard fashion.…”
Section: Comparison To Related Structuresmentioning
confidence: 73%
“…In CsHSO 4 (II) each XO 4 group is, by de®nition, a sulfate and hydrogen bonds exist only along the chain. The proton to XO 4 group ratio is 1:1 and, accordingly, two hydrogen bonds are formed per tetrahedral unit (Belushkin et al, 1991). InCs 3 (HSO 4 ) 2 (H 2 PO 4 ) every third XO 4 group along the chain is a phosphate group.…”
Section: Comparison To Related Structuresmentioning
confidence: 99%
“…For example, SO groups may take on multiple orientations, such that different oxygen atoms participate in H bonds in different orientations. Precisely this type of disorder is observed in the high-temperature, superprotonic structure of CsHSO (phase I) (16). Moreover, it is precisely this type of disorder-sulfate groups undergoing rapid reorientation-that facilitates proton transport and results in high conductivity.…”
Section: Hydrogen-bond Geometrymentioning
confidence: 98%
“…The special attention is paid to the crystals with hydrogen bonds that exhibit transition to superprotonic (superionic) phase with high conductivity that arises due to the motion of protons. Extensive experimental studies of these systems (see [2] for a review) revealed that the charge transfer occurs within the network of hydrogen bonds that connect ionic groups and form, in particular, quasi-one-dimensional (chain-like) [3][4][5] structures. For various crystals it was shown that superionic phase transition is driven by the transformation in proton subsystem (see [2] for review).…”
Section: Introductionmentioning
confidence: 99%